Aw qāla: Li-jārihi': some observations on brotherhood and neighborly love in Islamic tradition - Leirvik, Oddbjørn (Islam and Christian-Muslim relations, 2010)
The article takes its point of departure in A common word's quotation of two versions of the Golden Rule' in Hadith. One version speaks of wishing for your brother what you wish for yourself. The other refers to neighbor' instead of brother' (aw qāla: Li-jārihi' [or maybe he said: for the neighbor']). In the methodological perspective of conceptual history, the article examines the notions of neighbor' and brother' in Hadith, in the Qur'an, in classical and modern tafsīr, and in contemporary usage (as reflected in some Muslim web pages). The article is organized as a textual study, but historical-contextual perspectives are also considered. The underlying question is whether the notions of brother and neighbor signal a tension between communal solidarity and universal obligation in Islamic tradition. In conclusion, the question of brotherhood and neighborhood is also discussed in a gender-critical and interreligious perspective.